FROM HOME TO WHATSAPP: DIGITAL FAMILY LANGUAGE POLICY AND WAIJEWA LANGUAGE TRANSMISSION AMONG SUMBANESE MIGRANT FAMILIES IN KUPANG CITY - Christmas Prasetia Ate; Muliani (ELite Journal : International Journal of Education, Language and Literature, 2026)
This research examines digital family language policy and Waijewa language transmission among Sumbanese migrant families in Kupang City, East Nusa Tenggara, Indonesia. This study employed a qualitative-dominant embedded mixed-methods design, in which qualitative data from interviews and WhatsApp communication were used as the primary basis for interpretation, while questionnaire data provided descriptive quantitative support for identifying general patterns of language use and family language practices. The participants consisted of 28 Sumbanese migrant families with Waijewa-speaking backgrounds who live in Kupang City and use WhatsApp as part of their family communication. Data were collected through questionnaires, semi-structured interviews, and selected WhatsApp communication practices, then analyzed descriptively and thematically using the framework of family language policy, language maintenance and shift, and digital sociolinguistics. The findings show that Waijewa remains strongly used in communication with parents, elders, adult relatives, and during family gatherings. However, its use with children is less consistent, as many younger family members understand Waijewa but often respond in Indonesian or Kupang Malay. WhatsApp functions as an extended family domain through voice notes, video calls, family groups, greetings, jokes, advice, and emotional messages. Nevertheless, digital communication does not automatically guarantee active transmission unless younger speakers are encouraged to participate in Waijewa. The research concludes that Waijewa remains resilient as a language of identity, kinship, and emotional belonging, but its long-term vitality depends on consistent family language management and active youth participation.